The Role of Fintech in Islamic Banking and Finance - Adam Sa'ad, Auwal (2021)
 Islamic fintech could be defined as the use of innovative technologies in the design and delivery of Islamic Financial products and services.  Based on a projected CAGR of 15.3%, the global worth of the digital banking market’s of USD 5.2 billion as of end-2018 will reach USD16.2 billion by 2025.  In 2019, the financial technology (FinTech) industry attracted about USD 136 billion worth of global investments with 2,693 deals, including mergers and acquisitions, private equity and venture capital. This is because, more than 3.5 billion people around the world are connected to the mobile internet, with about 300 million people newly connected in 2018 alone. (IFSB)  The adoption of blockchain technology as a connectivity backbone in the digital transformation process of financial institutions is expected to have a potential impact exceeding USD 3.9 trillion by 2025.